Serum chemerin level in chronic kidney disease - Samiha Abo Eiyazeed Abd Rabo; Nagwa Abdel Ghaffar Mohamed; Naglaa Abd Elfattah Tawfik; Marwa Mosa Hamed (SpringerOpen, 2016)
Background Chronic kidney disease (CKD) is a progressive loss in renal function over a period of months or years. In the metabolic association of an elevated circulating chemerin level in the context of uremia demonstrate that high chemerin levels predict a better survival in CKD patients. The aim of the study was to measure serum chemerin and to correlate it with other parameters in CKD patients. Patients and methods This study was conducted on 40 patients with CKD, including 20 patients with end-stage renal disease under regular hemodialysis and 20 patients with renal impairment on conservative therapy who have not started hemodialysis, and 22 apparently healthy participants serving as the control group. Human chemerin is determined by sandwich enzyme immunoassay. Results There is a highly statistically significant difference in mean serum chemerin and mean serum high-sensitivity C-reactive protein (hs-CRP) in the patient groups in comparison with the control group. In addition, there was a highly statistically significant difference between control group, under hemodialysis group, and renal impairment group as regards serum chemerin and serum hs-CRP. A positive correlation between serum chemerin and hs-CRP studied in the under hemodialysis group, renal impairment group, and in all patients' group. Conclusion A significantly higher chemerin level in patients with impaired kidney function compared with the normal control group, and a high increase in patients under hemodialysis compared with the other two groups.